2014
DOI: 10.1155/2014/968723
|View full text |Cite
|
Sign up to set email alerts
|

Primary Signet Ring Cell Carcinoma of the Lung with Cerebellar Metastasis Showing Full Response to Cisplatin and Docetaxel Therapy

Abstract: Introduction. Primary signet ring cell carcinoma (SRCC) of the lung is a very rare disease. We describe a new case of primary SRCC of the lung with cerebellar metastasis, which responded well to the therapeutic approach with cisplatin and docetaxel. Case Report. A 41-year-old female patient (nonsmoker) was consulted to our oncology outpatient clinic after cerebellar metastasectomy. The histopathological diagnosis was SRCC metastasis. The primary tumor was unknown. The PET-CT imaging showed a hypermetabolic mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…Our patient failed to show any such driver mutation on next generation sequencing. In oncologic literature chemotherapeutic agents such as platinum based (cisplatin) and microtubule assembly destabilizer (docetaxel) also have been used with benefit to some extent however the prognosis of primary lung SRCC remains poor [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient failed to show any such driver mutation on next generation sequencing. In oncologic literature chemotherapeutic agents such as platinum based (cisplatin) and microtubule assembly destabilizer (docetaxel) also have been used with benefit to some extent however the prognosis of primary lung SRCC remains poor [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary SRCC of the lung is a very rare disease, originally described by Kish et al in 1989 [8]. The incidence varies from 0.14% to 1.9% of all lung cancers [9]. Tsuta et al reported on 2640 surgically resected primary lung carcinomas; 39 (1.5%) of these tumors showed SRCC components.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most lung cancers are adenocarcinomas, primary signet ring cell (adeno)carcinoma (SRCC) of the lung represents a rare uncommon condition, originally described by Kish et al in 1989 [8]. The incidence varies from 0.14% to 1.9% of all lung cancers [9].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these rearrangements has therapeutic significance, as tumors with ROS1 rearrangements and the EML4-ALK translocation have been shown to respond to the smallmolecule ALK inhibitor, crizotinib. [8][9][10] Here we report a case of primary lung SRCC presenting as a cavitary Pancoast tumor in a 32-year-old male smoker. Beyond the rarity of primary lung SRCC itself, we discuss several features of the case that make it noteworthy.…”
mentioning
confidence: 92%
“…The immunohistochemical staining profile for primary lung SRCC typically features positivity for TTF-1, CK7, and napsin A, with negativity for CK20 and CDX-2. 9,10 Primary lung SRCC has recently been associated with rearrangements of the ALK and ROS1 genes. A 2014 study by Boland et al 9 found ALK rearrangements in 14 of 53 SRCC cases (26%) and ROS1 rearrangements in 3 of 47 SRCC cases (6%).…”
mentioning
confidence: 99%